Fate, Providence and Free Will: Philosophy and Religion in Dialogue in the Early Imperial Age. - Brouwer, René,; Vimercati, Emmanuele, (Ancient Philosophy & Religion ;, 2020)
This volume, edited by René Brouwer and Emmanuele Vimercati, deals with the debate about fate, providence and free will in the early Imperial age. This debate is rekindled in the 1st century CE during emperor Augustus' rule and ends in the 3rd century CE with Plotinus and Origen, when the different positions in the debate were more or less fully developed. The book aims to show how in this period the notions of fate, providence and freedom were developed and debated, not only within and between the main philosophical schools, that is Stoicism, Aristotelianism, and Platonism, but also in the interaction with other, "religious" movements, here understood in the general sense of groups of people sharing beliefs in and worship of (a) superhuman controlling power(s), such as Gnosticism, Hermetism as well as Judaism and Christianity.